Fat distribution in children and adolescents with myelomeningocele. (23rd September 2014) - Mueske, Nicole M; Ryan, Deirdre D; Van Speybroeck, Alexander L; Chan, Linda S; Wren, Tishya AL
<x xml:space="preserve">Abstract</x> Aim To evaluate fat distribution in children and adolescents with myelomeningocele using dual‐energy X‐ray absorptiometry (DXA). Method Cross‐sectional DXA measurements of the percentage of fat in the trunk, arms, legs, and whole body were compared between 82 children with myelomeningocele (45 males, 37 females; mean age 9y 8mo, SD 2y 7mo; 22 sacral, 13 low lumbar, 47 mid lumbar and above) and 119 comparison children (65 males, 54 females; mean age 10y 4mo, SD 2y 4mo). Differences in fat distribution between groups were evaluated using univariate and multivariate analyses. Results Children with myelomeningocele had higher total body fat (34% vs 31%, p=0.02) and leg fat (42% vs 35%, p<0.001) than comparison children, but no differences in trunk or arm fat after adjustment for anthropometric measures. Interpretation Children with myelomeningocele have higher than normal total body and leg fat, but only children with higher level lesions have increased trunk fat, which may be caused by greater obesity in this group. Quantifying segmental fat distribution may aid in better assessment of excess weight and, potentially, the associated health risks.